Upaya Peningkatan Aktivitas Belajar Dan Keterampilan Memecahkan Masalah Menggunakan Model LEARN GREAT Pada Muatan IPA - Qurota Ayun; Ahmad Suriansyah; Ratna Purwanti (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The new era 5.0 causes challenges covering various aspects and fields, one of which is education. Therefore, it is necessary to have human resources who have high-level thinking skills (HOTS), where one of the supports is science subjects. However, in science learning in elementary schools, it is still found that student activity in learning and problem-solving skills and learning outcomes tend to be low. For this reason, this study aims to improve the activities of teachers, students, problem-solving skills and learning outcomes. This research uses Classroom Action Research Techniques (PTK) which was carried out in 3 meetings in class V of SDN Terantang 1 Barito Kuala Regency with a total of 10 students. Researchers use the LEARN GREAT LEARNing model, and collect data quantitatively and qualitatively, and analyze it in the form of tables and graphs. The results showed that student activity increased from a classical percentage score of 30% at meeting 1 to 100% at meeting 3, as well as problem-solving skills from a classical percentage score of 50% at meeting 1 to 100% at meeting 3. While cognitive learning outcomes increased from 70% to 90%. Based on the results of this study, it can be concluded that the use of the LEARN GREAT model can improve teacher activity, student activity, problem-solving skills and student learning outcomes.